CMET-01. CLINICAL AND DOSIMETRIC FACTORS RELATED TO RADIATION NECROSIS AFTER FIVE FRACTION RADIOSURGERY FOR RESECTED BRAIN METASTASES. (5th November 2018) - Buchwald, Zachary; Jhaveri, Jaymin; Schreibmann, Eduard; Switchenko, Jeffrey; Prabhu, Roshan; Chowdhary, Mudit; Abugideiri, Mustafa; Eaton, Bree; Olson, Jeffrey; Shu, Hui-Kuo; Crocker, Ian; Curran, Walter; et al.
Abstract: PURPOSE: Stereotactic Radiosurgery (SRS) is increasingly utilized in the management of resected brain metastases (rBM). A significant complication is radiation necrosis (RN) due to larger target size. Despite dose de-escalation and hypofractionation, rates of RN after SRS to rBM remain high. The aim of this analysis is to evaluate dosimetric parameters associated with RN for rBM. Methods: From 2008–2016, 55 rBM in 52 patients at a single institution that were treated with 5 fraction LINAC based SRS (25-35Gy) with a minimum 3 months follow-up were evaluated. For each lesion, variables including clinical target volume (CTV), dose and location/magnitude of hot spots were recorded. Hot spot location was stratified as either within tumor bed (CTV) or within the PTV expansion margin (PTV minus CTV). Overall survival (OS) estimated using Kaplan-Meier method. Cumulative incidence with competing risks was used to estimate rates of RN and local recurrence (LR). Optimal cut-points predicting for RN for hotspot magnitude based on location were identified via maximization of the log-rank test statistic. Results: Median age and OS for all patients was 58.5 years and 16.2 months, respectively. For all targets, the median CTV was 17.53 cc, and mean max hotspot was 113%. At 1 year, cumulative incidence of RN and LR for all patients was 21.8% and 13.1%. Univariate analysis showed max hot spot (hazard ratio (HR): 3.28, p=0.045) and hot spots within PTV expansion margin of 105%, 110% and 111% predicted for RN with HRs of 3.64, 8.47, and 6.90 respectively (all p<0.05), but hot spots within the CTV did not. Conclusion: To our knowledge, this is the first study that investigated dosimetric factors that predict for RN after hypofractionated SRS to rBM. Hot spot location and magnitude appear important for predicting RN risk, suggesting these parameters should be considered during treatment planning.